MORPHOLOGICAL CHARACTERISTICS OF RAT BRONCHI AGAINST THE BACKGROUND OF POST-TRAUMATIC STRESS DISORDER AND AFTER QUERCETIN CORRECTION - Bilash, S.M.; Koptev, M.M.; Pronina, O.M.; Pirog-Zakaznikova, A.V.; Oliinichenko, Ya.O.; Donchenko, S.V.; Kononov, B.S. (World of Medicine and Biology, 2024)
War affects the daily lives of the vast majority of Ukrainians. Therefore, post-traumatic stress disorder has become one of the most pressing medical and social problems in Ukraine today. It is characterised by a complex pathogenesis and comorbidity with many other diseases. Studying models of post-traumatic stress disorder in rats, its impact on various organs and systems, as well as finding ways to correct it are crucial for restoring the health of victims. The work presents the results of a morphological study of the effect of post-traumatic stress disorder on the rat bronchi and its correction with quercetin. It has been established that this disorder causes significant destructive changes in the large bronchi of rats, in particular, desquamation of epithelial cells with the formation of cellular detritus in the bronchial lumen, hyperhydration and leukocyte infiltration of the mucosa and submucosa, and haemomicrocirculation disorders. Intraperitoneal injection of water-soluble quercetin complex once a day for seven days in rats significantly reduced the damage to the large bronchi against the background of post-stress disorder, indicating this agent’s effectiveness as a stress protector.